Pengaruh Sertifikasi Halal Self Declare, Branding, Kreativitas Produk Terhadap Keberhasilan Usaha Kuliner di Teras Malioboro Yogyakarta - Nada Afifah; Al Haq Kamal; Rusny Istiqomah Sujono; Ahmad Yunadi (CV. Kalimasada Group, 2025)
The culinary industry in Teras Malioboro Yogyakarta is growing rapidly along with the increasing halal tourism. Halal certification self-declare, branding, and product creativity are important factors that influence the success of culinary businesses in facing competition and meeting Muslim consumer preferences. This study aims to analyze the effect of halal certification halal self-declaration, branding, and product creativity on the success of culinary businesses in the Malioboro Terrace area of Yogyakarta. The approach approach used is quantitative with multiple linear regression analysis method. Data obtained through distributing questionnaires to 40 culinary business actors who have met certain criteria, such as having culinary business actors who have met certain criteria, such as already having self-declare halal certification and operating for at least one year. The results The analysis shows that the variables of self-declare halal certification, branding, and product creativity partially and simultaneously have a significant effect on business success. Halal certification provides legal certainty and increase consumer confidence. Strong branding contributes to product product differentiation, while product creativity drives innovation and competitive advantage. These findings provide important implications for culinary venture, local governments, and other stakeholders in formulating strategies for the development of sharia-based development of sharia value-based culinary businesses in the leading tourist areas of Yogyakarta.